Monitorização terapêutica da ciclosporina oral em pacientes pós transplantados alogênico de células tronco hematopoiéticas - Medeiros, Jôseffer Wianey Trindade (2017)
In the allogeneic hematopoietic stem cell transplantation the cells come from a non-identical donor, requiring the use of immunosuppressive therapy with the intention to prevent a graft versus host disease, using cyclosporine with this purpose. Its serum determination is used as monitoring and serves of parameter to adjust the dose and guarantee the degree of immunosuppression. A study was carried out in an outpatient clinic of patients undergoing allogenic transplantation in the use of CsA to prevent graft versus host disease, to analyze as clinical and pharmacokinetic characteristics of the population. Therapeutic monitoring was performed based on the sérum dosage of cyclosporin obtained by chemiluminescence method, also, monitoring of the biochemical dosages referring to renal and hepatic functions and the adverse events inherent to CsA. Thus, it was possible to establish a relationship between the occurrence of adverse events events with the study parameter and also with the clinical condition of the patient. Thirteen patients were accompanied, 84.6% (11/13) had CsA serum dosage outside the therapeutic range, and 76.9% (10/13) in the least the biochemical dosage for renal and hepatic. Furthermore, a relationship between serum biochemical levels and serum levels of CsA was observed, with 61.5% (8/13) of the patients studied presented concomitant biochemical and CsA pharmacokinetics. The incidence of cyclosporine related adverse events may be a reflection of changes in CsA serum levels found. It was concluded that, the appearance of GvHD may indicate the non-effectiveness of the treatment and immunosuppression may be associated with a serum level lower than the therapeutic level and, in turn, the appearance of nephrotoxicity and hepatotoxicity, among others, may be associated with therapeutic effect.